PSmad3+/Olig2− expression defines a subpopulation of gfap-GFP+/Sox9+ neural progenitors and radial glia-like cells in mouse dentate gyrus through embryonic and postnatal development - Ohyama, Kyoji; Shinohara, Hiroshi M.; Omura, Shoichiro; Kawachi, Tomomi; Sato, Toru; Toda, Keiko (Frontiers in Neuroscience, 2023)
In mouse dentate gyrus, radial glia-like cells (RGLs) persist throughout life and play a critical role in the generation of granule neurons. A lage body of evidence has shown that the combinatorial expression of transcription factors (TFs) defines cell types in the developing central nervous system (CNS). As yet, the identification of specific TFs that exclusively define RGLs in the developing mouse dentate gyrus (DG) remains elusive.Here we show that phospho-Smad3 (pSmad3) is expressed in a subpopulation of neural progenitors in the DG. During embryonic stage (E14-15), pSmad3 was predominantly expressed in gfap-GFP-positive (GFP+ ) /Sox2+ progenitors located at the lower dentate notch (LDN). As the development proceeds (E16-17), the vast majority of pSmad3+ cells were GFP+/Sox2+/Prox1low+/Ki67+ proliferative progenitors that eventually differentiated into granule neurons. During postnatal stage (P1-P6) pSmad3 expression was obsereved in GFP+ progenitors and astrocytes. Subsequently, at P14-P60, pSmad3 expression was found both in GFP + RGLs in the subgranular zone (SGZ) and astrocytes in the molecular layer (ML) and hilus. Notably, pSmad3+ SGZ cells did not express proliferation markers such as PCNA and phospho-vimentin, suggesting that they are predominantly quiescent from P14 onwards. Significantly pSmad3+/GFP+ astrocytes, but not SGZ cells, co-expressed Olig2 and S100b. Together, pSmad3+/Olig2-expression serves as an exclusive marker for a specific subpopulation of GFP+ neural progenitors and RGLs in the mouse DG during both embryonic and postnatal period.